Straightforward Patterning of Functional Polymers by Sequential Nanosecond Pulsed Laser Irradiation - Edgar Gutiérrez-Fernández; Tiberio A. Ezquerra; Aurora Nogales; Esther Rebollar (Nanomaterials, 2021)
Laser-based methods have demonstrated to be effective in the fabrication of surface micro- and nanostructures, which have a wide range of applications, such as cell culture, sensors or controlled wettability. One laser-based technique used for micro- and nanostructuring of surfaces is the formation of laser-induced periodic surface structures (LIPSS). LIPSS are formed upon repetitive irradiation at fluences well below the ablation threshold and in particular, linear structures are formed in the case of irradiation with linearly polarized laser beams. In this work, we report on the simple fabrication of a library of ordered nanostructures in a polymer surface by repeated irradiation using a nanosecond pulsed laser operating in the UV and visible region in order to obtain nanoscale-controlled functionality. By using a combination of pulses at different wavelengths and sequential irradiation with different polarization orientations, it is possible to obtain different geometries of nanostructures, in particular linear gratings, grids and arrays of nanodots. We use this experimental approach to nanostructure the semiconductor polymer poly(3-hexylthiophene) (P3HT) and the ferroelectric copolymer poly[(vinylidenefluoride-co-trifluoroethylene] (P(VDF-TrFE)) since nanogratings in semiconductor polymers, such as P3HT and nanodots, in ferroelectric systems are viewed as systems with potential applications in organic photovoltaics or non-volatile memories.